Hubungan Antara Dukungan Sosial Orang Tua dengan Motivasi Belajar Siswa SDK St. Ursula Ende - Ansel, Maria Finsensia; Arafat, Siti (UNIB Press, 2021)
This study aims to determine the relationship between parental social support and learning motivation of elementary school students. This research was correlational research with a quantitative approach. The population in this study were students of SDK St. Ursula, amounting to 435 people and the sample were 80 students in 5 and 6 grades with a purposive sampling technique. The data collection method used a questionnaire with the measuring instrument that consisted of the scale of parents' social support and the scale of student learning motivation. Data analysis was carried out by using product moment correlation which was calculated using SPSS version 26. The results showed the r value of 0.624, which means that there is a significant positive relationship between parents' social support and student learning motivation at SDK St. Ursula where the higher the parents 'social support, the higher the learning motivation of elementary school students, and conversely the lower the parents' social support, the lower the learning motivation of elementary school students.